Ethnobotanical studies on rice landraces under on-farm conservation in Xishuangbanna of Yunnan Province, China - Fei Wang; Tao Sun; Shuai Yu; Chunhui Liu; Zhuo Cheng; Jianxin Xia; Longzhi Han (BMC, 2024)
Abstract Background A complex interaction and mutual influence exists among landscapes, cultures, and landraces, with rice culture being a typical embodiment of this relationship. The conservation of landraces operates alongside preserving traditional practices. The Xishuangbanna region stands out as a hub for the genetic diversity of landraces, boasting rich genetic resources. Despite the diverse rice resources in this region, a comprehensive and systematic study has not been undertaken. Methods From October to November 2023, we collected rice landraces under the on-farm conservation in 18 townships including Menghai, Mengla and Jinghong in Xishuangbanna. Employing semi-structured interviews and various methods, we investigated factors influencing the preservation and loss of rice landraces in the region. Statistical analysis was applied to the agronomic traits of collected local rice, encompassing indica or japonica, glutinous or non-glutinous, grain shape, and hull color as second category traits. The second category included quantitative traits like thousand grain weight and grain length. Rice diversity among different regions, traits, and ethnic groups was assessed using the Shannon-Wiener index. Additionally, clustering analysis via the UPGMA method depicted the distribution characteristics of the resources. Results A total of 70 rice landraces were collected in the Xishuangbanna region, each exhibiting distinct characteristics. Differences were observed across regions, trait, naming, and ethnic groups. Diversity analysis revealed that Mengla had the highest diversity, followed by Menghai, while Jinghong exhibited the lowest diversity. The second category of traits displayed broader diversity than the first, with the Dai people's glutinous rice showcasing greater diversity than other ethnic groups. Cluster analysis categorized the 70 samples into seven groups at a genetic distance of 1.15. Ethnobotanical interviews emphasized the rapid loss of rice landraces resources in Xishuangbanna, with indigenous ethnic cultures playing a vital role in the conservation of rice landraces. Dai traditions, in particular, played a crucial role in protecting glutinous rice resources, showcasing a mutual dependence between Dai culture and glutinous rice. Conclusions The rich natural environment and diverse ethnic cultures in Xishuangbanna have given rise to various rice landraces. The Dai, primary cultivators of glutinous rice with higher diversity, intertwine their traditional ethnic culture with the conservation of glutinous rice resources. At the same time, the preserving glutinous rice resources promotes the inheritance of Dai ethnic culture. However, rice landraces are facing the risk of loss. Hence, collecting and documenting rice landraces is crucial. Encourage local communities to sustain and expand their cultivation, promoting on-farm conservation. These measures contribute valuable germplasm and genes for rice breeding and serve as a means of cultural preservation.